Analyze Capital Structure In Kamal Sharia Pawnloyers And Wonokromo Pawntown Case Study - Ayu Oktoriza, Linda; Rahmawati, Nur Fitri (Takaza Innovatix Labs Ltd., 2023)
This study aims to analyze the effect of the capital structure on PT. Pegadaian (Persero) tbk. It can determine where the capital is obtained by going directly to the field. This study uses qualitative methods with various other literature. The pledge is a right obtained by a creditor for a movable object, which is handed over to him by a debtor or by another person on his behalf, and which gives the debtor the authority to take payment of said item in priority over other creditors, except for the cost of auctioning the item and the costs incurred to salvage it. Based on the research described by the researchers, it can be concluded that the existing capital structure of the two pawnshops is either sharia or conventional. The capital structure owned by these two pawnshops is purely from the State. Because this pawnshop company is a State-Owned Enterprise (BUMN), all the principal capital comes from the State.